Exome Resequencing Identifies Potential Tumor‐Suppressor Genes that Predispose to Colorectal Cancer. Issue 7 (20th May 2013) - Smith, Christopher G.; Naven, Marc; Harris, Rebecca; Colley, James; West, Hannah; Li, Ning; Liu, Yuan; Adams, Richard; Maughan, Timothy S.; Nichols, Laura; Kaplan, Richard; Wagner, Michael J.; et al.
<x xml:space="preserve">Abstract</x> We exomeresequenced 50 sporadic patients with advanced CRC. To identify predisposition alleles, we sought rare/novel germline truncating mutations in 1138 genes considered likely to play a role in colorectal tumorigenesis. Thirty‐two such mutations were identified, including an insertion in APC, thereby validating our approach. We sought somatic mutations in the corresponding genes in the CRCs of the patients harbouring the germline lesions and found biallelic inactivation of FANCM, LAMB4, PTCHD3, LAMC3 and TREX2, implicating their potential role in CRC‐predisposition. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>